Language, eros, being : kabbalistic hermeneutics and poetic imagination - Wolfson, Elliot R. (UPCC book collections on Project MUSE., 2005)
Not only a study of texts, 'Language, Eros, Being' explores the complex gender symbolism that permeates Kabbalistic literature.